Towards a new era of 2D materials-based multifunctional composite films: From innovation to evolution - Khalid, Muhammad Yasir; Umer, Rehan (Advanced industrial and engineering polymer research, 2025)
Novel 2D materials are now at the forefront of developing advanced multifunctional composite films, due to their fascinating properties. Particularly, graphene and MXene-based 2D materials are recognized as promising candidates for multifunctional materials, due to their ability to enhance structure–function relationships and integrate with laminated composites. As expected, high mass production from low-cost and facile fabrication techniques for multifunctional composite films plays a pivotal role in their practical applications. Herein, we have covered a broad spectrum of 2D materials overview, covering all contributions to this field and summarizing the most pertinent literature available for developing multifunctional composite films which are attractive for advanced aircraft applications. Moreover, the integrated functions of the 2D materials-based multifunctional composite films such as sensing and actuation behaviour, thermal conductivity, and electromagnetic interference (EMI) shielding effectiveness are explored and their mechanisms for superior performance are elucidated. Additionally, we critically discuss the prevailing challenges and offer perspectives on this rapidly advancing field. [Display omitted] •2D materials-based nanocomposites are systematically reviewed.•Types, preparation routes, and key multifunctional features of 2D materials-based nanocomposites are critically assessed.•Emerging applications of 2D materials-based multifunctional composites are summarized.•Some prevailing challenges and further directions are suggested.